2003
DOI: 10.1039/b306197c
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic microreactors based on TiO2-modified polyelectrolyte multilayer capsules

Abstract: Spatially confined photocatalytic microreactors for microheterogeneous photoreduction of metal ions from aqueous solutions have been developed. The microreactors consist of hollow micron-sized polyelectrolyte capsules with photoactive TiO2 nanoparticles incorporated in the walls. Additional improvements in metal photoreduction efficiency were achieved by filling the microcapsule cavity with a more effective electron donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…[16][17][18] However only a few reports involved TiO2-polymer capsules based on pre-fabricated NPs. 2,19,20 Here we propose a novel strategy of incorporating TiO2 in situ into LbL assembly to prepare multifunctional composite microcapsules that possess both ultrasound and UV responsive functionalities. Without using pre-fabricated TiO 2 NPs, inorganic/PE capsules were made by in situ nucleation and growth of TiO 2 inside or on the PE shell surfaces based on the hydrolysis of titanium butoxide (TIBO).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] However only a few reports involved TiO2-polymer capsules based on pre-fabricated NPs. 2,19,20 Here we propose a novel strategy of incorporating TiO2 in situ into LbL assembly to prepare multifunctional composite microcapsules that possess both ultrasound and UV responsive functionalities. Without using pre-fabricated TiO 2 NPs, inorganic/PE capsules were made by in situ nucleation and growth of TiO 2 inside or on the PE shell surfaces based on the hydrolysis of titanium butoxide (TIBO).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the immobilization of nanosized noble metal on semiconductor enhances its photocatalytic activities (Takagi et al 2001;Shchukin et al 2003;Sakamoto et al 2009). Thus, the study of semiconductor-metal nanocomposites has undergone enormous development over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of information accumulated to date has demonstrated that the use of polyelectrolyte nano-and microcapsules has opened up considerable possibilities for the design of a new class of chemical and biochemical reactors, the investigation into the specific features of the physical and chemical processes occurring in small volumes, the fabrication of new types of probes and highly sensitive sensors, and the development of original methods for separating mixtures of different organic and inorganic compounds, in particular, for extracting heavy-metal ions from various media [1,2,[7][8][9][10][11][12]. Very interesting results have been obtained using polyelectrolyte nano-and microcapsules as matrices for the preparation of metallic semipermeable shells with magnetic and conducting properties [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%